2011
DOI: 10.1103/physrevb.84.165135
|View full text |Cite
|
Sign up to set email alerts
|

Indefinite dielectric response and all-angle negative refraction in a structure with deeply-subwavelength inclusions

Abstract: The realization of mesoscopic media that mimic an ideal continuous indefinite material remains a challenging problem, particularly because current designs are plagued by spatial dispersion effects and are based on inclusions whose size may be a significant fraction of the wavelength. Here we show that a structure formed by an array of inductively loaded metallic rods terminated by metallic patches at both ends may enable to largely overcome these problems, and imitate more closely indefinite dielectric media w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…This occurs because a lumped inductance is combined in series with the distributed inductance of a wire, and hence leads to the increase of the total inductance of the system and to a decrease of the effective plasma frequency. 20 Conversely, a capacitive lumped load behaves effectively as a shunt negative inductive load, and thus contributes to lower the total inductance of the system and to an increase of the resonant frequency.…”
Section: Dispersion Behavior Of the Guided Modesmentioning
confidence: 99%
See 3 more Smart Citations
“…This occurs because a lumped inductance is combined in series with the distributed inductance of a wire, and hence leads to the increase of the total inductance of the system and to a decrease of the effective plasma frequency. 20 Conversely, a capacitive lumped load behaves effectively as a shunt negative inductive load, and thus contributes to lower the total inductance of the system and to an increase of the resonant frequency.…”
Section: Dispersion Behavior Of the Guided Modesmentioning
confidence: 99%
“…7,16,17 Here, we demonstrate the possibility of near-field imaging based on mushroom-type metamaterials, as a continuation of our previous work on the analysis of reflection/transmission properties, natural modes, and negative refraction in these structures. [18][19][20] The main motivation is that the previous studies 19,21,22 have shown that mushroom-type substrates can support strongly confined guided modes that to some extent mimic the role of surface plasmon polaritons at optics. Similar to conventional plasmons, these strongly localized waveswhich are sometimes designated by "spoof plasmons" [22][23][24] are rooted in the resonant interaction of the electromagnetic field and the charge density oscillations in metals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because the presence of metallic patches at the wire ends diminishes charge buildup in such a way that, upon homogenization, the mushroom structure can be treated as a uniaxial continuous Epsilon-Negative (ENG) material loaded with a capacitive grid of patches. Further, in [13] generalized additional boundary conditions (GABCs) have been derived for wire media terminated with distributed loads (metallic patch arrays acting as parallel loads to the wires) and lumped loads (arbitrary impedance insertions acting as series loads to the wires) or a combination of both at the junction, with the latter case presented in [18,19]. Although, the GABCs derived in [13] are applied at the wire-to-patch connection with the finite size of the patch (with certain restrictions imposed on the size of the gap between the patches with respect to the separation of adjacent patch arrays), these boundary conditions are valid only for perfect electric conductor terminations.…”
Section: Introductionmentioning
confidence: 99%